Development of a nanoparticle-assisted PCR assay for detection of bovine respiratory syncytial virus - Liu, Zhankui (BMC Vet Res, 2019)
BACKGROUND: Bovine respiratory syncytial virus (BRSV) is a common pathogen causing respiratory disease in cattle and a significant contributor to the bovine respiratory disease (BRD) complex. BRSV is widely distributed around the world, causing severe economic losses. This study we established a new molecular detection method of BRSV pathogen NanoPCR attributed to the combination of nano-particles in traditional PCR (Polymerase chain reaction) technology. RESULTS: In this study, the BRSV NanoPCR assay was developed, and its specificity and sensitivity were investigated. The results showed that no cross-reactivity was observed for the NanoPCR assay for related viruses, including the infectious bovine rhinotracheitis virus (IBRV), bovine viral diarrhea virus (BVDV), and bovine parainfluenza virus type 3 (BPIV3), and the assay was more sensitive than the conventional PCR assay, with a detection limit of 1.43 × 10(2) copies recombinant plasmids per reaction, compared with 1.43 × 10(3) copies for conventional PCR analysis. Moreover, thirty-nine clinical bovine samples collected from two provinces in North-Eastern China, 46.15% were determined BRSV positive by our NanoPCR assay, compared with 23.07% for conventional PCR. CONCLUSIONS: This is the first report to demonstrate the application of a NanoPCR assay for the detection of BRSV. The sensitive and specific NanoPCR assay developed in this study can be applied widely in clinical diagnosis and field surveillance of BRSV infection.